Service Quality Parameters for Mobile Government Services in India. (February 2016) - Chanana, Lovneesh; Agrawal, Rajat; Punia, Devendra Kumar
Information and communications technology (ICT)-based government service delivery in India is rapidly achieving a stage of maturity. With the increasing teledensity and the penetration of mobile devices, the Indian central and state governments have started to offer government services over mobile devices. As more and more government services are offered over mobile phones, it is important to gain an understanding of parameters determining the quality of mobile government services. The identification of service quality parameters will help stakeholders appropriately prioritize and position mobile-based government service delivery. This article presents the findings of an exploratory study using an online survey of Indian e-government experts on the service quality parameters for m-government in India. The study aims to identify and prioritize the service quality parameters based on similar parameters identified by researchers for e-government and mobile service quality.